The Relationship Trunk Extension Flexibility, Body Height, and Arm Explosive Power Students’ Volleyball Serving Skills - Akhmad, Noor; Bausad, Andi Anshari; Hasanuddin , M Imran (LITPAM, 2022)
Smash ability in sepaktakraw is a complex attacking skill that requires the integration of anthropometric reach, lower-limb explosive power, flexibility, body coordination, and technical accuracy. This study aimed to examine the relationship between leg length, leg explosive power, and flexibility with smash ability among students of the Faculty of Sport Science, Universitas Negeri Makassar. A quantitative approach with a descriptive-correlational design was employed. The final sample consisted of 50 students with complete data and no missing values. Leg length was measured using an anthropometric procedure, leg explosive power using the vertical jump test, flexibility using a trunk flexibility test, and smash ability using a sepaktakraw smash skill test. The data were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, Pearson correlation, simple regression, and multiple regression. The findings showed that leg length, leg explosive power, and flexibility were positively and significantly related to smash ability, with correlation coefficients of r = 0.552, r = 0.676, and r = 0.607, respectively. The multiple regression model indicated that the three predictors simultaneously explained 60.9% of the variance in smash ability. These findings indicate that sepaktakraw smash performance is more strongly supported by functional physical capacities, particularly lower-limb explosive power and flexibility, than by anthropometric characteristics alone.